Czy to koniec zawodów prawniczych w Europie - przykład Polski - Antkowiak, Paweł (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The subject of this article is access to legal services in Europe, demonstrated on the basis of Polish solutions in the field. The legal professions operate as corporations called professional self-government. The theoretical assumptions behind professional self-government is that it guarantees high ethical and professional standards, as well as balance between free professional practice and the quality of services provided. Its existence and operation is therefore an integral part of the democratic rule of law.